1991
DOI: 10.1104/pp.97.1.433
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Chitinase Gene Promoter by Ethylene and Elicitors in Bean Protoplasts

Abstract: Chitinase gene expression has been shown to be transcriptionally regulated by a number of inducers, including ethylene, elicitors, and pathogen attack. To investigate the mechanism(s) responsible for induction of chitinase gene expression in response to various stimuli, we have developed a transient gene expression system in bean (Phaseolus vulgaris) protoplasts that is responsive to ethylene and elicitor treatment. This system was used to study the expression of a chimeric gene composed of the 5' flanking seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…We have shown that for induction by TMV infection of tobacco genes encoding a glycinerich protein and an acidic PR-5 protein upstream sequences of 650 bp and over 1 kb are required, respectively (Albrecht et a/., 1992; Van de Rhee et a/., 1990). A 5' deletion analysis of a bean chitinase promoter showed that the region between -305 and -236 is necessary for induction by ethylene and fungal elicitor treatment in bean protoplasts (Roby et a/., 1991). For the Arabidopsis acidic chitinase promoter it was found that 192 bp upstream of the transcription start site are sufficient for inducible expression following fungal infection and salicylate treatment in transgenic Arabidopsis plants (Samac and Shah, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that for induction by TMV infection of tobacco genes encoding a glycinerich protein and an acidic PR-5 protein upstream sequences of 650 bp and over 1 kb are required, respectively (Albrecht et a/., 1992; Van de Rhee et a/., 1990). A 5' deletion analysis of a bean chitinase promoter showed that the region between -305 and -236 is necessary for induction by ethylene and fungal elicitor treatment in bean protoplasts (Roby et a/., 1991). For the Arabidopsis acidic chitinase promoter it was found that 192 bp upstream of the transcription start site are sufficient for inducible expression following fungal infection and salicylate treatment in transgenic Arabidopsis plants (Samac and Shah, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…ln fact, a chitinase gene in rice cellsuspension cultures is induced by a fungal cell wall elicitor (Zhu & Lamb, 1991), whereas an endochitinase gene from bean is regulated by chitin oligomers und cell-wall fragments from Colletotrichum lage/iariurn (Roby et al, 1991), or infection with C. lindemuthianum (Hedrick et al, 1988).…”
Section: In Man)" Plants Poly-and Oligosaccharide Degrading Enzymes Smentioning
confidence: 99%
“…As observed with the stable transgenic lines, deletions into the EAS4 promoter brought about a quantitative decrease in GUS expression. Moreover, in spite of the high background of GUS expression that was presumably due to the elicitation occurring during the preparation of the protoplasts (Roby et al, 1991;Mohan et al, 1993), the protoplasts were able to respond to a subsequent elicitor treatment. The levels of GUS activity for 5' deletions to -567, -212, and -160 were significantly elevated by the elicitor treatment and were approximately 2-fold greater than the GUS activity measured in protoplasts not receiving additional elicitor.…”
Section: Gttcatcaaagtggactctgcattaataattgaaatttatgccgcaacaa T G a C Amentioning
confidence: 99%